2022
DOI: 10.1021/acs.jpcc.2c01743
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Facet-Dependent Anisotropy in Halide Perovskite Single Crystals

Abstract: Metal halide perovskite (MHP) single crystals (SCs) are proven to possess superior optoelectronic properties compared to those of their polycrystalline thin film analogues. With the advancement and progress in the study of MHP SCs, it is found that the properties at the surface and bulk of SCs are significantly different. However, there are only a few studies present for the facet-dependent performance of MHP SCs. In this work, we have systematically investigated the anisotropic properties of naturally exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The photocurrent increases with light intensity due to higher photocarrier generation at higher light intensities (Figure b). We have also calculated the responsivity ( R ) and detectivity ( D ) of the single-crystal detectors according to the following equations Here, I p is the photocurrent, I D is the dark current, S is the active area of the detector, and P j is the power of incident light …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photocurrent increases with light intensity due to higher photocarrier generation at higher light intensities (Figure b). We have also calculated the responsivity ( R ) and detectivity ( D ) of the single-crystal detectors according to the following equations Here, I p is the photocurrent, I D is the dark current, S is the active area of the detector, and P j is the power of incident light …”
Section: Resultsmentioning
confidence: 99%
“…We have also calculated the responsivity (R) and detectivity (D) of the single-crystal detectors according to the following equations Here, I p is the photocurrent, I D is the dark current, S is the active area of the detector, and P j is the power of incident light. 39 The maximum values of R and D are 12.35 mA/W and 5.89 × 10 9 Jones, respectively. The corresponding EQE = hc/eλ (where h is the Planck constant, c is the speed of light, and λ is the wavelength of illuminated light) of these detectors is 38.8% at 5 V.…”
Section: Transient Photovoltagementioning
confidence: 93%
“…This results in a relatively high defect density on the surface than on the bulk region . In view of this, the exact nature of traps and their effect on the optoelectronic properties are under active investigation. Many efforts have been devoted to passivate the defects to increase the stability and performance of the halide perovskite SCs. To this end, one approach is to treat the crystals with various Lewis acid- or base-based ligands after synthesis ,, or to control the growth of SCs using additives. , Duim et al investigated the mechanism of surface passivation of methylammonium lead tribromide (MAPbBr 3 ) SCs using benzylamine, and it was reported that exposure to benzylamine results in the formation of two-dimensional (2D) (BA) 2 PbBr 4 on the surface of a three-dimensional (3D) perovskite by replacing the methylammonium cations .…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies in the case of electronic and dielectric properties across various faces of the synthesized MAPbBr 3 crystals are due to structural defects, and these could be due to multiple types of defects. For example, density functional theories have been performed on various halide perovskite crystals to understand defects such as Frenkel defects due to the absence of Pb 2+ , I – , or MA + vacancies, and Schottky pair defects are due to PbBr 2 or MAI defects that do not generate trap states. Since the current reaches the saturation domain for the more significant path along face III, contradicting the I–V nature across the crystals, we further investigated the correlations between electron transport and structural characterization across the various faces of our synthesized MAPbBr 3 crystals.…”
Section: Resultsmentioning
confidence: 99%